Histone Methyltransferase Setd7 Regulates Nrf2 Signaling Pathway by Phenethyl Isothiocyanate and Ursolic Acid in Human Prostate Cancer Cells. Issue 18 (6th March 2018) - Wang, Chao; Shu, Limin; Zhang, Chengyue; Li, Wenji; Wu, Renyi; Guo, Yue; Yang, Yuqing; Kong, Ah‐Ng
Abstract : Scope: This study aims to investigate the role of the epigenetic regulator SET domain‐containing lysine methyltransferase 7 (Setd7) in regulating the antioxidant Nrf2 pathway in prostate cancer (PCa) cells and examines the effects of two phytochemicals, phenethyl isothiocyanate (PEITC) and ursolic acid (UA). Methods and results: Lentivirus‐mediated shRNA knockdown of Setd7 in LNCaP and PC‐3 cells decreases the expression of downstream Nrf2 targets, such as NAD(P)H: quinone oxidoreductase 1 (Nqo1) and glutathione S‐transferase theta 2 (Gstt2). Downregulation of Setd7 decreases soft agar colony formation ability of PCa cells. Knockdown of Setd7 increases reactive oxygen species (ROS) generation. Furthermore, Setd7 knockdown attenuates Nqo1 and Gstt2 expression in response to H2 O2 challenge, whereas increased DNA damage is observed in Setd7 knockdown cells in comet assay. Interestingly, Setd7 expression could be induced by the dietary phytochemicals PEITC and UA. Chromatin immunoprecipitation (ChIP) assays show that Setd7 knockdown decreased H3K4me1 enrichment in the Nrf2 and Gstt2 promoter regions, while PEITC and UA treatments elevated the enrichment. Conclusion: Taken together, these results indicate that Setd7 knockdown decreases Nrf2 and Nrf2‐target genes expression and that PEITC and UA induce Setd7 expression, which activates the Nrf2/antioxidant response element (ARE) signaling pathway and protects DNA from oxidative damage. Abstract : Setd7 knockdown decreases the expression of downstream Nrf2 targets Nqo1 and Gstt2 and soft agar colony formation ability. Knockdown of Setd7 increases ROS generation and attenuates Nqo1 and Gstt2 expression in response to H2 O2 challenge, whereas it increases DNA damage. Setd7 expression could be induced by PEITC and UA. Setd7 knockdown decreases H3K4me1 enrichment in Nrf2 and Gstt2 promoter regions.